FIS (Fun-Innovative-Spritual): Manajemen Pemasaran di KB. Fun Islamic School Purworejo - HMS, Deden (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2020)
Speaking of course school management has been widely discussed and has become a very interesting topic from year to year. The discussion is often focused on classroom management, financial administration and institutional structures and learning systems in schools. That's all the material is in internal management. This research will focus on the discussion of external management namely how an institution is able to build a brand and partnership with the community, and other institutions and then how the institution increases trust in the community and others. The success of an Eqrly Childhood Education institution is actually in external management. However, there are many institutions that have never paid attention to this, so that many Early Childhood Education instituttion are left behind and are not in demand by the community. For this reason, researcher will focus on how to build the success of an institution with the right management FIS (Fun-Innovative and spirituality).